“A rua é nóis”: um panorama da criação, significação e disputas das e nas ruas de Fortaleza (1863-1932) - Moreira, Maria Isabele Farias (2023)
This work aims to understand the processes of construction, production, meaning and disputes in and around the streets of the city of Fortaleza between 1863 and 1932. For cities, the streets are an important part of the exchanges and events of everyday urban life, the encounters between people and the construction of an urban logic of sociability of their own. The streets are a diffuse object; they don't have clear boundaries as to who walks, works, plays and practices all kinds of activities in their daily life. Likewise, their structural configurations are also heterogeneous: sidewalks, paving, lighting, all of which vary according to location and, above all, according to the power games that are established around the significance of this space. For the analysis of this work, we used the city plans of the architect and urban planner Adolfo Herbster, periodicals widely linked to the period, building codes, documents from the municipal administration, censuses and texts by memorialists. Aiming to achieve greater diversity through an exercise in street cartography, the work has the following objectives: to analyze the process of street formation as a fundamental urban space and to understand the contradictions between the planned streets and the real city. We conclude that no street is in meaning, when consumed, what was attributed to it in genesis, but rather a continuous process of signification by all those who make up this space.